Pendidikan Islam Dan Dinamika Politik Kebangsaan Di Indonesia - Mutiah; Muhammad Roihan Alhaddad; Dwi Noviani (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
Education in essence is a conscious effort of all parties to internalize the noble values ​​both taught by religious teachings and Pancasila to all children of the nation. The formation of character in order to strengthen the nation's civilization is an important goal of education. the function of Islamic Education is a means to provide facilities that can enable the task of Islamic education to be achieved and run smoothly. Religious education has received serious attention from the government, both in public and private schools. Religious education has received serious attention from the government, both in public and private schools. Education in essence is a conscious effort of all parties to internalize the noble values ​​both taught by religious teachings and Pancasila to all children of the nation. The formation of character in order to strengthen the nation's civilization is an important goal of education. The Commission for Education and Regeneration of the Indonesian Ulema Council (MUI) feels the need and is called upon to convey several views to the wider community, especially regarding the impact of political dynamics on education